Irish English as a World English - Kirk, John (Frontiers in Communication, 2022)
The objective of this chapter is to apply a synthesis of models for world Englishes to Irish English, for which data from ICE-corpora, the Handbook of Varieties of English, the Mouton Atlas, eWAVE, and the GloWbE corpus are used, and to which many approaches are applied: geo-political, dynamic-model, corpus, statistical, and multi-functional factor analysis. The chapter's relevance lies in its bringing together wide-ranging and seemingly disparate material through the lens of Irish English as a common denominator. The chapter shows the difficulties of applying top-down models to empirical corpus data and concurs that the gap is ultimately unbridgeable. Nevertheless, in so far as status distinctions can be inferred, this chapter also concurs with the many different findings that, as a standardized variety, despite a historical legacy of contact, Irish English is indeed an L1.